Change in the Finnish healthcare: managerial sensemaking in the private sector. (2015) - Lammassaari, Maarit; Hiltunen, Esa
This intensive case study explored managerial sensemaking during a change in the Finnish healthcare. In order to achieve the purpose of the study, an interview was carried out with a manager acting in the private healthcare sector while major political decisions about the future of the healthcare system were waited in the healthcare field. A sensemaking perspective was adopted as a methodological tool for analysing the interview data. Healthcare change is perceived as an uncertain and a constant change environment for the private healthcare sector. The social change is greatly impacting on the changes occurring in the companies. Our paper provides a way of understanding healthcare changes and furthers the empirical use of sensemaking as a method.